Analysis Of The Influence Of Store Atmosphere, Celebrity Endorsers And Pricing On Purchase Decisions Of American Fast Food Customers In Indonesia - Suparman; Zunan Setiawan; Salamatun Asakdiyah; Sarwo Eddy Wibowo; Eva Yuniarti Utami (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The dependent variable in this study is purchase decisions (Y), while the independent factors are celebrity endorser (X1), store environment (X2), and pricing (X3). Multiple linear regression analysis is the technique utilized for analysis. The sample for this study consisted of 60 participants who were chosen at random among customers. According to the study's findings, pricing, shop ambiance, and celebrity endorsers all have an impact on consumers' purchase decisions at the same time. The study's findings also indicate that the influence of pricing, shop ambiance, and celebrity endorsers on purchase decisions is only marginally significant. According to the coefficient of determination, the independent variables (celebrity endorser, shop ambiance, and price) had a 36.6% effect on the dependent variable (buy decision). 63.4%, meanwhile, is affected by other factors and is left out of this regression study.